2014
DOI: 10.1007/s11356-014-3395-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and enzymatic activity of soil contaminated with a mixture of diflufenican + mesosulfuron-methyl + iodosulfuron-methyl-sodium

Abstract: The aim of this study was to determine the effect of three active substances, diflufenican, mesosulfuron-methyl and iodosulfuron-methyl-sodium, applied in combination, on soil microbial counts, the structure of soil microbial communities, activity of soil enzymes and their resistance to the tested product, the biochemical indicator of soil fertility, and spring wheat yield. Soil samples with the granulometric composition of sandy loam with pHKCl 7.0 were used in a pot experiment. The herbicide was applied to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 56 publications
4
39
0
1
Order By: Relevance
“…Atrazine, primextra, paraquat and glyphosate also had a negative effect on the development of bacteria, actinomycetes and fungi, according to Sebiomo et al (2011). In contrast, Baćmaga et al (2015) following the use of a mixture of active substances named diflufenican, mesosulphuron-methyl and iodosulphuron-methyl-sodium observed an increase in the counts of total oligotrophic bacteria and their spore forms, organotrophic bacteria and actinomycetes, and a decrease in the counts of fungi and Azotobacter. Martinez et al (2008) studying sulfentrazone found that this product stimulates the growth of actinomycetes, but it does not have an effect on the count of fungi.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Atrazine, primextra, paraquat and glyphosate also had a negative effect on the development of bacteria, actinomycetes and fungi, according to Sebiomo et al (2011). In contrast, Baćmaga et al (2015) following the use of a mixture of active substances named diflufenican, mesosulphuron-methyl and iodosulphuron-methyl-sodium observed an increase in the counts of total oligotrophic bacteria and their spore forms, organotrophic bacteria and actinomycetes, and a decrease in the counts of fungi and Azotobacter. Martinez et al (2008) studying sulfentrazone found that this product stimulates the growth of actinomycetes, but it does not have an effect on the count of fungi.…”
Section: Resultsmentioning
confidence: 87%
“…In five repetitions, the respective dilutions of soil were sown onto Petri dishes. On the media characterised by Baćmaga et al (2015).…”
Section: Determination Of the Soil Microorganism Countsmentioning
confidence: 99%
“…Dehydrogenase activity (DHA) from sediment was determined using 2, 3, 5-triphenyltetrazolium chloride (TTC) as substrate (Neto et al 2007;Bacmaga et al 2015). The fresh sediment was diluted with sterilized distilled water to 1:2 (w/ v), adding 2 ml Tris-HCl (pH 7.5) and 2 ml 0.4 % TTC to the 2 ml of the suspension liquid.…”
Section: Methods Enzyme Analysismentioning
confidence: 99%
“…The soil enzyme activity reacts faster than physical activity of soil. Therefore, they can beused as an early warning bioindicator against the changes occur in soil (Baćmaga et al, 2015;Franco-Andreu et al, 2016;Saha Ajoy et al, 2016. So far, contrasting results have been observed by various researchers evaluating the impact of imazethapyr on soil microbial biomass and enzymatic activities.…”
Section: Introductionmentioning
confidence: 99%